The Relationship Between Self-Control, Time Management, and Authoritarian Parenting on Students’ Academic Procrastination - Minati, Rima Wahyu; Ruhaena, Lisnawati (Universitas Islam Indonesia, 2025)
The integration of online learning greatly affects final-year students who are working on their thesis. One common challenge they face is academic procrastination. This quantitative study aimed to examine the relationship between self-control, time management, and authoritarian parenting on students’ academic procrastination. A total of 350 final-year students from the Universitas Muhammadiyah Surakarta were selected as participants through a convenience sampling method. Data was collected using scales for academic procrastination, self-control, time management, and authoritarian parenting. Data was analyzed using multiple regression, resulting in an F-value of 94.506 and a p-value of .000. The results showed that selfcontrol, time management, and authoritarian parenting were significantly correlated with academic procrastination. The beta coefficients for self-control and academic procrastination, as well as time management and academic procrastination, were negative, with values of -.286 and -.261, respectively. This indicated that high self-control and time management could reduce academic procrastination. Moreover, authoritarian parenting showed a significant value of .069, suggesting that students getting exposed to higher levels of such parenting style were more likely to engage in academic procrastination. The effective contribution of self-control, time management, and authoritarian parenting to academic procrastination was found to be 45%. Thus, improving self-control could be an effective strategy for reducing academic procrastination.